Prevention of Varicella and Zoster by vaccination: Now you see it, now you don't - Gershon, Anne (Henry Stewart Talks, 2018)
Varicella zoster virus (VZV) pathology and disease progressions, Clinical VZV infections, History of live attenuated varicella vaccine and importance of this vaccine, Mechanisms of viral latency and reactivation, Subclinical reactivation, Latency of VZV in the enteric nervous system (ENS) and resulting gastrointestinal disease, Vaccination against herpes zoster